Silico substrate specificity in bmgt1 and bmgt2 genes of bacopa monniera glycosyltransferases online journal of bioinformatics - Sharma, Ranu; Ruby; Khan, Bashir Mohammad; Suresh, C.G. (Bioinformatics, 2011)

Genome-wide identification and tissue-specific expression analysis of nucleotide binding site-leucine rich repeat gene family in Cicer arietinum (kabuli chickpea) - Sharma, R.; ,Rawat, V.; Suresh, C.G. (Genomics Data, 2017)
The nucleotide binding site-leucine rich repeat (NBS-LRR) proteins play an important role in the defense mechanisms against pathogens. Using bioinformatics approach, we identified and annotated 104 NBS-LRR genes in chickpea. Phylogenetic analysis points to their diversification into two families namely TIR-NBS-LRR and non-TIR-NBS-LRR. Gene architecture revealed intron gain/loss events in this resistance gene family during their independent evolution into two families. Comparative genomics analysis elucidated its evolutionary relationship with other fabaceae species. Around 50% NBS-LRRs reside in macro-syntenic blocks underlining positional conservation along with sequence conservation of NBS-LRR genes in chickpea. Transcriptome sequencing data provided evidence for their transcription and tissue-specific expression. Four cis-regulatory elements namely WBOX, DRE, CBF, and GCC boxes, that commonly occur in resistance genes, were present in the promoter regions of these genes. Further, the findings will provide a strong background to use candidate disease resistance NBS-encoding genes and identify their specific roles in chickpea.

Structural insights into the unique inhibitory mechanism of Kunitz type trypsin inhibitor from Cicer arietinum L. - Bendre, A.D.; Suresh, C.G.; Shanmugam, D.; Ramasamy, S. (Journal of Biomolecular Structure and Dynamics, 2018)
Kunitz-type trypsin inhibitors bind to the active pocket of trypsin causing its inhibition. Plant Kunitz-type inhibitors are thought to be important in defense, especially against insect pests. From sequence analysis of various Kunitz-type inhibitors from plants, we identified CaTI2 from chickpea as a unique variant lacking the functionally important arginine residue corresponding to the soybean trypsin inhibitor (STI) and having a distinct and unique inhibitory loop organization. To further explore the implications of these sequence variations, we obtained the crystal structure of recombinant CaTI2 at 2.8Å resolution. It is evident from the structure that the variations in the inhibitory loop facilitates non-substrate like binding of CaTI2 to trypsin, while the canonical inhibitor STI binds to trypsin in substrate like manner. Our results establish the unique mechanism of trypsin inhibition by CaTI2, which warrant further research into its substrate spectrum. Abbreviations BApNA Nα-Benzoyl-L-arginine 4-nitroanilide BPT bovine pancreatic trypsin CaTI2 Cicer arietinum L trypsin inhibitor 2 DrTI Delonix regia Trypsin inhibitor EcTI Enterolobium contortisiliquum trypsin inhibitor ETI Erythrina caffra trypsin inhibitor KTI Kunitz type inhibitor STI soybean trypsin inhibitor TKI Tamarindus indica Kunitz inhibitor Communicated By Ramaswamy H. Sarma.